Development and application of an efficient genomic mating method to maximize the production performances of three-way crossbred pigs. Issue 1 (28th December 2022) - Tang, Zhenshuang; Yin, Lilin; Yin, Dong; Zhang, Haohao; Fu, Yuhua; Zhou, Guangliang; Zhao, Yunxiang; Wang, Zhiquan; Liu, Xiaolei; Li, Xinyun; Zhao, Shuhong
Abstract: Creating synthetic lines is the standard mating mode for commercial pig production. Traditional mating performance was evaluated through a strictly designed cross-combination test at the 'breed level' to maximize the benefits of production. The Duroc–Landrace–Yorkshire (DLY) three-way crossbred production system became the most widely used breeding scheme for pigs. Here, we proposed an 'individual level' genomic mating procedure that can be applied to commercial pig production with efficient algorithms for estimating marker effects and for allocating the appropriate boar-sow pairs, which can be freely accessed to public in our developed HIBLUP software at https://www.hiblup.com/tutorials#genomic-mating . A total of 875 Duroc boars, 350 Landrace–Yorkshire sows and 3573 DLY pigs were used to carry out the genomic mating to assess the production benefits theoretically. The results showed that genomic mating significantly improved the performances of progeny across different traits compared with random mating, such as the feed conversion rate, days from 30 to 120 kg and eye muscle area could be improved by −0.12, −4.64 d and 2.65 cm 2, respectively, which were consistent with the real experimental validations. Overall, our findings indicated that genomic mating is an effective strategy to improve the performances of progeny by maximizing their total genetic merit with consideration of both additive and dominant effects. Also, a herd of boars from a richer genetic source will increase the effectiveness of genomic mating further.